Long-Term Follow-Up of Disability, Cognitive, and Emotional Impairments after Severe Traumatic Brain Injury - Britt-Marie Stålnacke; Britt-Inger Saveman; Maud Stenberg (Behavioural Neurology)
Aim. To assess the clinical course of disability, cognitive, and emotional impairments in patients with severe TBI (s-TBI) from 3 months to up to 7 years post trauma. Methods. A prospective cohort study of s-TBI in northern Sweden was conducted. Patients aged 18-65 years with acute Glasgow Coma Scale 3-8 were assessed with the Glasgow Outcome Scale Extended (GOSE), the Hospital Anxiety and Depression Scale (HADS), and the Barrow Neurological Institute Screen for Higher Cerebral Functions (BNIS) at 3 months, 1 year, and 7 years after the injury. Results. The scores on both GOSE and BNIS improved significantly from 3 months (GOSE mean: 4.4±2.3, BNIS mean: 31.5±7.0) to 1 year (GOSE mean: 5.5±2.7, p=0.003, BNIS mean: 33.2±6.3, p=0.04), but no significant improvement was found from 1 year to 7 years (GOSE mean: 4.7±2.8, p=0.13, BNIS mean: 33.5±3.9, p=0.424) after the injury. The BNIS subscale “speech/language” at 1 year was significantly associated with favourable outcomes on the GOSE at 7 years (OR=2.115, CI: 1.004-4.456, p=0.049). Conclusions. These findings indicate that disability and cognition seem to improve over time after s-TBI and appear to be relatively stable from 1 year to 7 years. Since cognitive function on some of the BNIS subscales was associated with outcome on the GOSE, these results indicate that both screening and follow-up of cognitive function could be of importance for the rehabilitation of persons with s-TBI.